Uses of Cornus Species in Alternative Medicine: Minireview - Khafaji, Noor S. K. Al-; Mahdi, Zena Abdul-Ameer; Dahmoshi, Hussein O.M. Al-; Akram, Muhammad; Tahir, Imtiaz Mahmood; Laila, Umme; Zainab, Rida; Khalil, Muhammad Talha; Iftikhar, Momina; Ozdemir, Fethi Ahmet; Sołowski, Gaweł; Ahandani, Ebrahim Alinia-; et al. (Jour Med Resh and Health Sci, 2023)
Background: Despite the wide range of synthetic drugs, natural way of treatment in traditional medicine always remained valuable. Objectives: In this review article, plants of Cornus species along with their beneficial uses as healing mixture in traditional medicine has been studied and discussed. Methods: Literature was searched through Google Scholar, Science Direct and Cochrane database etc. Discussion: Cornus species consists of almost 65 plants. Plants belonging to this cornaceae family typically are trees or shrubs .They all play different roles in different ways. Some plants are being used in horticulture for decoration and in gardening purpose. Few plants with their medicinal uses are described in this paper. Different plants have different action against different diseases as anti-proliferators, anti-diabetic, anti-oxidant, anti-inflammatory, tumor cell proliferation inhibition, cyclooxygenase enzymes inhibition, lipid peroxidation, inhibition of nitric oxide production, anti-fungal, anti-bacterial, anti-viral, anti-plasmodial, anti-microbial and oxygen free radical scavenging activity. Conclusion: This review indicates that use of natural extracts in medicine or treatment with plants and medicinal herb is considered best due to their cost effectiveness, minimal or no side effects and better action in their target site.